Implementasi Peraturan Daerah Nomor 2 Tahun 2013 Tentang Penataan dan Pemberdayaan Pedagang Kaki Lima (PKL) di Kawasan Alun-Alun Kota Pasuruan Jawa Timur - Ellysia Eka Putri Agustina; Radjikan Radjikan; Muhammad Roisul Basyar (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
Pasuruan City has an economic dynamic driven by the informal sector, especially street vendors (PKL), which play a crucial role in supporting the community's economy. One of the locations that is the center of street vendor activities is the Pasuruan City Square area. Despite its strategic value, the presence of street vendors in the area has caused problems related to order, cleanliness, and public space management. In response, the Pasuruan City Government has enacted Local Regulation No. 2/2013 on the Arrangement and Empowerment of Street Vendors. This study aims to analyze the implementation of the policy and identify factors that support and hinder its implementation. This research uses a descriptive qualitative approach by referring to Van Meter and Van Horn's policy implementation theory, which includes six main indicators. Data collection techniques were conducted through interviews, observation, documentation, and literature study. The results show that policy implementation is quite effective, as seen from the addition of official locations, assistance with facilities such as carts, and entrepreneurship training. However, challenges remain, mainly related to limited human resources and low compliance of street vendors with zoning regulations.